Speciation Analysis of Gadolinium in the Water-Insoluble Rat Brain Fraction After Administration of Gadolinium-Based Contrast Agents. Issue 9 (2nd September 2021) - Strzeminska, Izabela; Factor, Cécile; Robert, Philippe; Szpunar, Joanna; Corot, Claire; Lobinski, Ryszard
Abstract : Supplemental digital content is available in the text. Abstract : Purpose: To date, the analysis of gadolinium (Gd) speciation in the brain of animals administered with macrocyclic and linear Gd-based contrast agents (GBCAs) has been limited to Gd soluble in mild buffers. Under such conditions, less than 30% of the brain tissue was solubilized and the extraction recoveries of GBCAs into the aqueous phase were poor, especially in the case of the linear GBCAs. The aim of this study was to find the conditions to solubilize the brain tissue (quasi-)completely while preserving the Gd species present. The subsequent analysis using size exclusion chromatography–inductively coupled plasma–mass spectrometry (SEC-ICP-MS) was intended to shed the light on the speciation of the additionally recovered Gd. Methods: Four groups of healthy female Sprague Dawley rats (SPF/OFA rats; Charles River, L'Arbresle, France) received randomly 5 intravenous injections (1 injection per week during 5 consecutive weeks) of either gadoterate meglumine, gadobenate dimeglumine, gadodiamide (cumulated dose of 12 mmol/kg), or no injection (control group). The animals were sacrifice 1 week (W1) after the last injection. Brain tissues were solubilized with urea solution, whereas tissues extracted with water served as controls. Total Gd concentrations were determined in the original brain tissue and its soluble and insoluble fractions by inductively coupled plasma–mass spectrometry (ICP-MS) to calculate the Gd accumulation and extraction efficiency. Size exclusion chromatography coupled to ICP-MS was used to monitor the speciation of Gd in the soluble fractions. The stability of GBCAs in the optimum conditions was monitored by spiking the brain samples from the untreated animals. The column recoveries were precisely determined in the purpose of the discrimination of weakly and strongly bound Gd complexes. The identity of the eluted species was explored by the evaluation of the molecular size and retention time matching with Gd chelates and ferritin standard. The speciation analyses were carried out for 2 different brain structures, cortex and cerebellum. Results: The combination of water and urea extractions (sequential extraction) managed to solubilize efficiently the brain tissue (97% ± 1%) while preserving the stability of the initially injected form of GBCA. For macrocyclic gadoterate, 97% ± 1% and 102% ± 3% of Gd initially present in the cortex and cerebellum were extracted to the soluble fraction. For gadobenate, similar amounts of Gd (49% ± 1% and 46% ± 4%) were recovered from cortex and cerebellum. For gadodiamide, 48% ± 2% of Gd was extracted from cortex and 34% ± 1% from cerebellum. These extraction efficiencies were higher than reported elsewhere. The SEC-ICP-MS and the column recovery determination proved that Gd present at low nmol/g levels in brain tissue was exclusively in the intact GBCA form in all the fractions of brain from the animals treated with gadoterate. For the linear GBCAs (gadobenate and gadodiamide), 3 Gd species of different hydrodynamic volumes were detected in the urea-soluble fraction: (1) larger than 660 kDa, (2) approximately 440 kDa, and (3) intact GBCAs. The species of 440 kDa corresponded, on the basis of the elution volume, to a Gd 3+ complex with ferritin. Gd 3+ was also demonstrated by SEC-ICP-MS to react with the ferritin standard in 100 mM ammonium acetate (pH 7.4). In contrast to macrocyclic gadoterate, for linear GBCAs, the column recovery was largely incomplete, suggesting the presence of free, hydrolyzed, or weakly bound Gd 3+ with endogenous ligands. Conclusions: The sequential extraction of rat brain tissue with water and urea solution resulted in quasi-complete solubilization of the tissue and a considerable increase in the recoveries of Gd species in comparison with previous reports. The macrocyclic gadoterate was demonstrated to remain intact in the brain 1 week after administration to rats. The linear GBCAs gadobenate and gadodiamide underwent ligand exchange reactions resulting in the presence of a series of Gd 3+ complexes of different strength with endogenous ligands. Ferritin was identified as one of the macromolecules reacting with Gd 3+ . For the linear GBCAs, 3% of the insoluble brain tissue was found to contain more than 50% of Gd in unidentified form(s).